The Inconsistencies in Efforts to Realize Gender Equality Towards the Roles of Husband and Wife to Fulfill Economic Needs in Relation to Positive Law in Indonesia - Nur Hasanah Ariyanti; Sonny Dewi Judiasih; Nyulistiowati Suryanti (Dinasti Research, 2024)
: Gender equality is one of the human rights issues that until now still cannot be realized properly, including in marriage. Gender injustice in marriage scope arises due to the existence of differences in roles, rights, and obligations between husband and wife. These differences have a significant impact on the role and freedom of wives in the public sector, particularly in their efforts to fulfill the economic needs of their families. Gender injustice still occurs because there are inconsistencies in efforts to realize gender equality. Therefore, it became the author's concern because it hinders the realization of gender equality. This research used the method of normative juridical research by presenting supporting data in the form of interviews with several wives who have dual roles as housewives and breadwinners in the industrial located in Solokan Jeruk, Bandung Regency and shoe craft centers located in Cibaduyut, Bandung City. The results show that there are inconsistencies in efforts to realize gender equality in the scope of marriage related to fulfilling family economic needs, that is, inconsistencies in efforts to realize gender equality in marriage law in Indonesia, between marriage law and other positive laws, and positive laws and implementation in real life.